Spectroscopic Study on Charge-Spin-Orbital Coupled Phenomena in Mott-Transition Oxides - Uchida, Masaki (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
In this thesis the author presents the results of extensive spectroscopy experiments beyond the bounds of each transition element to clarify the origins of characteristic spectral features and charge dynamics in charge-spin-orbital coupled phenomena in Mott-transition oxides. Several counterpart 3d transition-metal oxides were adopted as model systems suitable for examining the mechanisms involved, and their electronic structures were systematically investigated using three main spectroscopy methods. Comparative studies on the charge dynamics and Mott transition features of transition-metal oxides were performed: Charge dynamics and thermoelectricity in a typical Mott transition system La1-XSrXVO3, charge dynamics in a doped valence-bond solid system (Ti1−xVx)2O3 and in layered nickelates R2-xSrxNiO4 with charge-ordering instability are investigated thoroughly. The results obtained successfully provide a number of novel insights into the emergent phenomena near the Mott transition.  .